Adjuvant denosumab in postmenopausal patients with hormone receptor-positive breast cancer (ABCSG-18): disease-free survival results from a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 3 (March 2019) - Gnant, Michael; Pfeiler, Georg; Steger, Günther G; Egle, Daniel; Greil, Richard; Fitzal, Florian; Wette, Viktor; Balic, Marija; Haslbauer, Ferdinand; Melbinger-Zeinitzer, Elisabeth; Bjelic-Radisic, Vesna; Jakesz, Raimund; et al.
Summary: Background: In postmenopausal women with hormone receptor-positive, early-stage breast cancer, treatment with adjuvant aromatase inhibitors is the standard of care, but it increases risk for osteoporosis and fractures. Results from the ABCSG-18 trial showed that use of denosumab as an adjuvant to aromatase inhibitor therapy significantly reduced clinical fractures. Disease-free survival outcomes from ABCSG-18 have not yet been reported. Methods: Postmenopausal patients with early, hormone receptor-positive, non-metastatic adenocarcinoma of the breast, who had completed their initial adjuvant treatment pathway (surgery, radiotherapy, or chemotherapy, or a combination) and were receiving adjuvant aromatase inhibitors, were enrolled at 58 trial centres in Austria and Sweden into this prospective, double-blind, placebo-controlled, phase 3 trial. With permuted block randomisation (block sizes 2 and 4, stratified by previous aromatase inhibitor use, total lumbar spine bone mineral density score at baseline, and type of centre), patients were assigned (1:1) to receive subcutaneous denosumab (60 mg) or matching placebo every 6 months during aromatase inhibitor therapy. The primary endpoint (previously reported) was the time to first clinical fracture after randomisation. The secondary endpoint reported here is disease-free survival (defined as time from randomisation to first evidence of local or distant metastasis, contralateral breast cancer, secondary carcinoma, or death from any cause) in the intention-to-treat population. This study is registered with EudraCT (number 2005–005275–15) and ClinicalTrials.gov (number NCT00556374 ), and is ongoing for long-term follow-up. Findings: Between Dec 18, 2006, and July 22, 2013, 3425 eligible patients were enrolled and randomly assigned; 1711 to the denosumab group and 1709 to the placebo group (with five others withdrawing consent). After a median follow-up of 73 months (IQR 58–95), 240 (14·0%) patients in the denosumab and 287 (16·8%) in the placebo group had disease-free survival events. Disease-free survival was significantly improved in the denosumab group versus the placebo group (hazard ratio 0·82, 95% CI 0·69–0·98, Cox p=0·0260; descriptive analysis, without controlling for multiplicity). In the denosumab group, disease-free survival was 89·2% (95% CI 87·6–90·8) at 5 years and 80·6% (78·1–83·1) at 8 years of follow-up, compared with 87·3% (85·7–89·0) at 5 years and 77·5% (74·8–80·2) and 8 years in the placebo group. No independently adjudicated cases of osteonecrosis of the jaw or confirmed atypical femoral fractures were recorded. The total number of adverse events was similar in the denosumab group (1367 [including 521 serious] adverse events) and the placebo group (1339 [515 serious]). The most common serious adverse events were osteoarthritis (62 [3·6%] of 1709 in the denosumab group vs 58 [3·4%] of 1690 in the placebo group), meniscus injury (23 [1·3%] vs 24 [1·4%]), and cataract (16 [0·9%] vs 28 [1·7%]). One (<0·1%) treatment-related death (due to pneumonia, septic kidney failure, and cardiac decompensation) occurred in the denosumab group. Interpretation: Denosumab constitutes an effective and safe adjuvant treatment for patients with postmenopausal hormone receptor-positive early breast cancer receiving aromatase inhibitor therapy. Funding: Amgen.